Novel catalyst-free synthesis of vertically aligned silicon nanowire-carbon nanotube heterojunction arrays for high performance electron field emitters - Kale, Vinayak S.; Sathe, Bhaskar R.; Kushwaha, Ajay; Aslam, Mohammed; Shelke, Manjusha V. (Chemical Communications, 2011)
A novel, catalyst-free strategy for the direct synthesis of vertically aligned silicon nanowire-carbon nanotube (SiNW-CNT) heterojunction arrays is presented. Such a heterojunction with the junction area in the nanoscale displays enhanced field emission characteristics at low turn-on field, with a nearly three times increase in the field enhancement factor.